INTEGRATED ENVIRONMENTAL FOOTPRINT INDEX (IEFI): MODEL DEVELOPMENT AND VALIDATION - Silva,Vicente De P. R. Da (2017)
ABSTRACT: Freshwater is a valuable resource worldwide given the growing demand of the global population. This study aimed to develop and validate an integrated assessment model by means of environmental footprint indices (water, ecological, and carbon), which measure the environmental sustainability of heterogeneous communities, people, and countries. An environmental footprint was firstly defined as a set of indicators to track human pressure on planet Earth under different angles, being a multidimensional index of environmental sustainability. A Delphi survey was used to bring together opinions from a diverse set of experts. The participants of this study consisted of 120 experts from several fields of knowledge belonging to the best-known research and education institutions in Brazil. Through this technique, an integrated environmental footprint index (IEFI) could be developed, being then validated with information from eight different communities located in the Paraíba State (Brazil). Afterwards, this index was applied to several representative countries from all continents. Our results indicated the sensitiveness of IEFI model to variations in natural ecosystems, in addition to its ability to identify the environmental balance of a person, community, or nation level.